2013
DOI: 10.1590/s0100-69912013000600014
|View full text |Cite
|
Sign up to set email alerts
|

Excesso de peso em pacientes submetidos ao transplante hepático

Abstract: ABSTRACT ABSTRACT ABSTRACTThis review aims to describe the incidence and prevalence of overweight and obesity after liver transplantation and the consequences associated with it. Literature review consultation was conducted in Medline / PubMed, SciELO, EMBASE and LILACS, with the combination of the following keywords: liver transplantation, overweight, obesity, weight gain. Overweight is incident on more than 60% of patients undergoing liver transplantation and obesity rates exceed 20% in the first year after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(66 reference statements)
0
5
0
4
Order By: Relevance
“…Despite the controversy on what occurs with sarcopenia after LTx, it is well known that patients gain too much weight and become obese after surgery. The median weight gain in the three years after the operation is 11.6±8.7 kg 1 , and the majority of the patients after LTx are overweight or obese 2 . Thus, one may wonder if the weight gain after LTx is a reflection of sarcopenic obesity and not necessarily an improvement in nutritional health 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the controversy on what occurs with sarcopenia after LTx, it is well known that patients gain too much weight and become obese after surgery. The median weight gain in the three years after the operation is 11.6±8.7 kg 1 , and the majority of the patients after LTx are overweight or obese 2 . Thus, one may wonder if the weight gain after LTx is a reflection of sarcopenic obesity and not necessarily an improvement in nutritional health 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Alguns fatores contribuem para os pós-transplantados hepáticos terem ganho de peso acima do normal, associados ao uso dos medicamentos imunossupressores, como a dislipidemia e a hiperglicemia ou diabetes pós-transplante (10) . Sendo assim, a equipe multiprofissional deve promover programas de prevenção do ganho de peso excessivo durante o acompanhamento desses pacientes (22) .…”
Section: Resultsunclassified
“…Trabalho realizado no 1 ABSTRACT -Background: The treatment of choice for patients with schistosomiasis with previous episode of varices is bleeding esophagogastric devascularization and splenectomy (EGDS) in association with postoperative endoscopic therapy. However, studies have shown varices recurrence especially after long-term follow-up.…”
Section: Mensagem Centralmentioning
confidence: 99%
“…Portanto, há evidências de expressivo ganho de peso associado à terapia imunossupressora pós-transplante em humanos 1,4,13,14 .…”
Section: Introductionunclassified